2019
DOI: 10.1091/mbc.e18-09-0604
|View full text |Cite
|
Sign up to set email alerts
|

Local, transient tensile stress on the nuclear membrane causes membrane rupture

Abstract: Cancer cell migration through narrow constrictions generates compressive stresses on the nucleus that deform it and cause rupture of nuclear membranes. Nuclear membrane rupture allows uncontrolled exchange between nuclear and cytoplasmic contents. Local tensile stresses can also cause nuclear deformations, but whether such deformations are accompanied by nuclear membrane rupture is unknown. Here we used a direct force probe to locally deform the nucleus by applying a transient tensile stress to the nuclear mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 55 publications
(72 reference statements)
2
57
0
Order By: Relevance
“…Super-resolution imaging studies have suggested that the size of holes in ruptured nuclear membranes is of the order of 100 nm (Denais et al, 2016). This experimental evidence is supported by estimates of the hole size from measurements of the kinetics of fluorescent probe decay from the nucleus upon rupture (Zhang et al, 2019). These sizes are much larger than hole sizes for single bilayer membranes, which tend to be of the order of a few nanometers.…”
Section: Extreme Bending Of the Nuclear Envelopementioning
confidence: 90%
See 1 more Smart Citation
“…Super-resolution imaging studies have suggested that the size of holes in ruptured nuclear membranes is of the order of 100 nm (Denais et al, 2016). This experimental evidence is supported by estimates of the hole size from measurements of the kinetics of fluorescent probe decay from the nucleus upon rupture (Zhang et al, 2019). These sizes are much larger than hole sizes for single bilayer membranes, which tend to be of the order of a few nanometers.…”
Section: Extreme Bending Of the Nuclear Envelopementioning
confidence: 90%
“…Importance of nuclear membrane mechanics in the context of nuclear rupture Single lipid membranes are only able to undergo 2-5% areal stretch, beyond which they rupture (Rawicz et al, 2000). A recent development relevant in the context of nuclear membrane mechanics is that fused nuclear membranes have also been observed to undergo rupture in cells (Denais et al, 2016;Hatch and Hetzer, 2016;Raab et al, 2016;Zhang et al, 2019). Membrane rupture is detrimental to cells as it exposes nuclear contents to the cytoplasm and vice versa, causing DNA damage, which has negative consequences for cell function (Denais et al, 2016;Irianto et al, 2017).…”
Section: Extreme Bending Of the Nuclear Envelopementioning
confidence: 99%
“…However, here we are primarily concerned with morphology in regards to general nuclear shape. A variety of metrics have been used to quantify changes in nuclear morphology, such as area strain (percent change in projected cross-sectional area) (Zhang et al 2019) and 3D irregularity (ratio of excess volume of a fitted convex hull to nuclear volume) (Tocco et al 2018). Aside from the previously noted connections to disease, nuclear morphology has further been linked to levels of transcriptional activity as nuclei with reduced volume enter a more quiescent state (Damodaran et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear membrane rupture in micropipette aspiration experiments has been attributed to tensile stresses at the anterior periphery of the nucleus [59,62]. Similar results have been recapitulated by Cao et al [3] in their model where they proposed that the front edge of the nucleus might be susceptible to tensile-stress induced damage during migration through ECM-like environments.…”
Section: Discussionmentioning
confidence: 55%